2017
DOI: 10.3389/fmicb.2017.02386
|View full text |Cite
|
Sign up to set email alerts
|

Effective Antimicrobial Activity of Plectasin-Derived Antimicrobial Peptides against Staphylococcus aureus Infection in Mammary Glands

Abstract: Staphylococcus aureus (S. aureus) is the causative agent for a wide variety of illnesses ranging from minor skin infections to life-threatening diseases. Development of antibiotic resistance by the bacteria has rendered many antibiotics ineffective. It has been known that plectasin-derived antimicrobial peptides (AMPs; NZ2114 and MP1102) are promising alternatives to antibiotics. However, their activities against S. aureus in mammary glands were unknown. Our objective was to assess the antimicrobial activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…Additionally, after treatment with the peptides or vancomycin, polymorphonuclear neutrophils disappeared from the alveoli (Fig. 7), which is consistent with the findings from previous studies 23 . It was also observed that the peptides NZ2114/H2 and vancomycin can protect the mammary glands of the mice from S. aureus infection.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, after treatment with the peptides or vancomycin, polymorphonuclear neutrophils disappeared from the alveoli (Fig. 7), which is consistent with the findings from previous studies 23 . It was also observed that the peptides NZ2114/H2 and vancomycin can protect the mammary glands of the mice from S. aureus infection.…”
Section: Discussionsupporting
confidence: 92%
“…It has been demonstrated that polyhexamethylene biguanide, plectasin, NZ2114, and MP1102 have a high efficiency against intracellular S. aureus in keratinocytes, human THP-1 and mouse RAW264.7 macrophages 17,21,22,33 . The bovine mammary epithelial MAC-T cells have been widely used to study the physiological function of breast tissues, screen for effective drugs, and simulate the actual conditions of bovine mastitis 23 . The results of this study showed that H2 displayed a strong ability to kill the three different internalized S. aureus strains in MAC-T cells, which was equal to that of NZ2114, but superior to that of vancomycin (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[109][110][111] While commercial development was halted, preclinical studies are actively ongoing with promising results. [112][113][114][115][116] Oragenics (Tampa, FL, USA) has investigated…”
Section: Systemic Antibioticsmentioning
confidence: 99%